Development of cost-effective proton exchange membrane using agro waste-based biochar for application in microbial fuel cell (MFC) - Bar A.; Kupkar O.J.; Upadhyay C.; Singh R.S. (My University, 2025)
Microbial fuel cell (MFC) is a promising emerging technology in which waste can be converted into energy, hydrogen and many other valuable products. Proton exchange membrane (PEM) contributes a significant portion (around 50%) of the overall cost of MFC. The current study focuses on synthesizing low-cost PEM using biochar produced by biomass pyrolysis at 400 °C. The Pristine biochar (PB) obtained by pyrolysis was sulphonated to improve the desirable properties required for the preparation of PEM. Brunauer-Emmet-Teller (BET) measurements show a considerable improvement in surface area per unit weight and decreased sulphonated biochar (SB) micropore size. FTIR analysis shows that the peak position is at 1169 cm−1, which indicates the presence of the sulphonyl group (-SO3H) in the SB. The presence of the group demonstrated that the sulphonation of biochar by sulphuric acid was done successfully. A comparison of proton conductivity between SB and PB was determined by Nyquist plot using Zsimp Win 3.21 software and the data taken from electrochemical impedance spectroscopy (EIS) measurements. A large improvement in the proton conductivity of SB (0.135 S cm−1) was observed compared to that of PB (0.0204 S cm−1). The morphological structure of PB and SB was studied using the scanning electron microscope (SEM). The SEM results showed more even pore distribution and the presence of pores and crevices on the SB than PB, which promotes better proton transfer. EDX results show the presence of sulphur in SB, which confirms the results of FTIR. Polyvinyl alcohol was used as a binder for the membrane preparation. The maximum power density of the MFC with SB-based PEM was found to be 5.6 mWcm−1. The estimated cost of the material was found to be 17 times cheaper than Nafion. This study demonstrated that biochar-based PEM can drastically lower the MFC’s overall cost. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.